Assessment of TAPI's Programs in invention commercialization - De Vera, Teresita O. (University of the Philippines Diliman, 2012)
Inventions and innovations are crucial to a country's efforts towards economic progress. The translation of inventive ideas into functional and useful invention products through commercialization needs relevant support and assistance from the government. It has been declared to be the Philippines' national policy "to give priority to invention and its utilization on the country's productive systems and national life and to this end, provide incentives to inventors and protect their exclusive right to their invention, particularly when the invention is beneficial to the people and contributes to national development and progress". The Technology Application and Promotion Institute (TAPI), a service agency under the Department of Science and Technology (DOST), is at the forefront in the implementation of Republic Act No. 7459 or the "Inventors and Invention Incentives Act of the Philippines" to provide assistance to Filipino inventors aimed at accelerating the development and commercialization of their inventions. As mandated under the law, the government shall provide a program that would give encouragement and support to inventors and maximize their capability and productivity through incentives and other forms of assistance and support. Among others, TAPI administers the Invention Development Assistance Fund for the initial experiments and prototype development and other invention-development related activities to assist inventors in the development and commercialization of their inventions. As the main implementing agency of R.A. No. 7459, TAPI is tasked with the carrying out of various programs of assistance to inventors such as the Invention Guarantee Fund, Intellectual Property Rights Assistance Program, Testing Assistance, Tax and Duty Exemption, Inventors Forum and Consulation, Tax and Duty Exemption, Inventors Forum and Consultation, Travel Assistance, Publication and Promotion Assistance, Invent school Program, National Invention Contest and Exhibits, Prototyping and Pilot Plant Assistance Programs, all intended as support services in the various stages of invention development. TAPI's Invention Development Division is responsible in administering the various programs of assistance to inventors to accelerate the development and commercialization of Filipino inventions. The implementation of two of its current programs, namely, the Invention-Based Enterprise Development Program and the Industry-Based Invention Development Programs has been reviewed to assess TAPI's approach in providing assistance in the commercialization of Filipino inventions. The transition of invention from idea into a commercial product is a challenge to both the inventors and the government agencies assisting them. Invention commercialization is a complex process and at every stage, there are difficulties that should be faced and overcome to finally enter the market. It is important that from the earliest stage, the market should already be considered as a key element, as most of the failures in commercializing an invention are attributed to market problems. Every stage in the commercialization process is a decision point on whether to continue development or drop the technology and at each stage government support is needed to translate the invention concept to a commercial product or process. A careful review of the current status of the programs brings to light the factors that contribute to the success and failures of the assisted invention projects. The study identifies improvements to increase chances of commercial success of assisted inventions and allow the allocation of resources for the development of invention products that will generate economic opportunities. The study has also considered the commercialization support provided to inventors in other countries particularly in Israel, Australia, Korea, Japan, India and the United States and recommends some practices or policies that can be adopted here. The recommendations are meant to improve the implementation of the programs to enhance the level of success of the funded invention projects. Moving the invention from the early stage of development to commercialization requires not only funding but also other forms of government support particularly in the further development, promotion and marketing of inventions, in order to enhance the inventor's capability in successfully commercializing their inventions.